2004
DOI: 10.1007/s00442-004-1671-7
|View full text |Cite
|
Sign up to set email alerts
|

Using stable hydrogen and oxygen isotope measurements of feathers to infer geographical origins of migrating European birds

Abstract: Successful application of stable-hydrogen isotope measurements (deltaDf) of feathers to track origins of migratory birds and other wildlife requires a fundamental understanding of the correlation between deltaDf and deuterium patterns in rainfall (deltaDp) over continental scales. A strong correlation between deltaDp and deltaDf has been confirmed for birds and insects in North America, but not yet for other continents. Here, we compare deltaDf data from resident European birds to new deltaDp basemaps for Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 34 publications
(51 reference statements)
7
190
1
2
Order By: Relevance
“…Although with few data corresponding to Hap-B, feathers belonging to both haplogroups showed H/D ratio corresponding to a wide range (from -86.8 to -33.8) of European rainfalls H/D values as mapped in Hobson et al (2004). However, the isotopic analysis highlighted a geographic differentiation of wintering individuals on the basis of their breeding origin: a clear separation between Northern (including Croatian samples) and Southern Italy (including Bulgarian samples) appeared.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Although with few data corresponding to Hap-B, feathers belonging to both haplogroups showed H/D ratio corresponding to a wide range (from -86.8 to -33.8) of European rainfalls H/D values as mapped in Hobson et al (2004). However, the isotopic analysis highlighted a geographic differentiation of wintering individuals on the basis of their breeding origin: a clear separation between Northern (including Croatian samples) and Southern Italy (including Bulgarian samples) appeared.…”
Section: Resultsmentioning
confidence: 89%
“…Feathers H/D ratios were compared with a European rainfalls H/D ratio map (Hobson et al 2004) to infer the breeding origin of Italian samples. Analysis of H/D ratio was performed following Clegg et al (2003) protocol at the Geoscience and Georesources Institute of National Research Council, Pisa, Italy.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The larger pyrrhula race is known to be irruptive (Riddington & Ward 1998, Newton 2002) and ringing recoveries from Finland show that birds have occurred at localities between 1900 and 2350 km apart in different winters (Newton in press). Stable isotope analysis of feathers collected from birds caught in Denmark and elsewhere has been undertaken to see whether this technique can identify the regions of origin of these birds, as the isotope signatures reflect those in the environment where the feathers were grown (Hobson et al 2004). These results showed that large birds involved in the 2004 influx came from a wide geographical area, although this technique failed to identify differences between trumpeting and normalcalling large Bullfinches (Newton et al in press).…”
Section: Originsmentioning
confidence: 99%